Proposal of a visual environment to support SCRUM - Kussunga, Fidel (2019)
Agile methodologies are increasingly considered important in the current context because of their focus on business benefit, strong stakeholder involvement and rapid incorporation of changing requirements. The Scrum methodology presents a generic and agile model for software development, but there are some gaps regarding solution architecture and requirements modeling and traceability. Fast customer feedback and support for volatile requirements result in higher product value, however, initial requirements modelling using modelling techniques are not commonly used in agile processes such as Scum to prepare the phase of Implementation of the software project.This article presents a first proposal for a visual environment to support the product / sprint backlog, helping to prioritize, track and decide on the most valuable, aligned and quickly deployable requirements.